Evaluating the predictive value of doublecortin as a marker for adult neurogenesis in canaries (Serinus canaria). Issue 6 (15th April 2014) - Vellema, Michiel; Hertel, Moritz; Urbanus, Susan L.; Van der, Annemie; Gahr, Manfred
ABSTRACT Doublecortin (DCX) is an important microtubule‐associated protein involved in the migration of young neurons into the cortical layers of the brain during early human development. The continued expression of DCX in brain areas with protracted neuron recruitment has promoted this endogenous protein as a popular indirect tool to monitor adult neurogenesis in a variety of species. However, little is known about its possible involvement in other cellular processes and a thorough validation of DCX as a quantitative measure for neurogenesis is generally lacking. Here we investigated the relationship between DCX expression and neuron recruitment in the brains of adult canaries (Serinus canaria), a species well‐known for its adult neurogenesis. We examined the age and functional state of DCX‐labeled cells by using mitotic and neuron‐specific markers, retrograde tracings, and immediate early gene colocalizations. Although DCX expression was high in brain areas implicated in adult neurogenesis, DCX‐expressing neurons were also abundant in regions that do not recruit new neurons. Moreover, DCX expression was observed in adult, active neurons, differentiated projection neurons, and birth‐dated neurons of up to 1 year of age. Season and testosterone treatment affected DCX expression in two song control nuclei, HVC and Area X, but did not correlate with known patterns of neuron recruitment. Together, these results demonstrate that DCX expression is not exclusive to young migrating neurons, and does not predict neuron recruitment equally throughout the canary brain. Therefore, DCX labeling needs careful validation for each brain region separately in each species analyzed when used to quantify adult neurogenesis. J. Comp. Neurol. 522:1299–1315, 2014. © 2013 Wiley Periodicals, Inc.